Levels of C-Reactive Proteins in Pregnant Women and its Relation with Preeclampsia in Singleton Pregnancy - Nasreen Akhtar, Arifa Zafar, Qurat-Ul-Ain, Tuba Rasheed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find the levels of C-reactive protein pregnant women and its relation with preeclampsia in singleton pregnancy. Study Design: Case control study. Place and Duration of Study: Department of Obstetrics & Gynaecology, Mohtarma Benazir Bhutto Shaheed Medical College, Mirpur Azad Kashmir from 1st July 2021 to 30th June 2022. Methodology: One hundred preeclampsia and 50 control women were enrolled. Protein in the urine presenting renal impairment, decrease platelet counts and renal disease were assessed. Cases that had a blood pressure which was chronically high in cases prior to gestation or were chronic renal disease patients were excluded from the study. A biochemical analysis of C-reactive proteins was conducted through ELISA. The results were than interpreted in terms of their association with preeclampsia. Demographic details and clinical parameters as body mass index (kg/m2), familial history, any related comorbidities, clinical signs and symptoms were documented. Results: The mean age of the preeclampsia women was 31.3±3.2 years while that of pregnant women who were normal controls as 25.8±3.8 years. Primigravida was higher in preeclampsia women while multigravida was higher in normal control pregnant women. Hypertension was prevalent in 73% of the preeclampsia cases than 10% of the normal control pregnant cases. Urinary protein was high as 2 gm in 51% cases of preeclampsia The C-reactive protein value was also significantly higher in preeclampsia cases than normal controlled pregnant women. Conclusion: There is a direct significant association between preeclampsia and high levels of C-reactive proteins. Keywords: C-reactive protein, Pre-eclampsia, Pregnancy